1982
DOI: 10.1007/bf00399486
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts in the intertidal sediments of a polluted estuary in Rio de Janeiro, Brazil

Abstract: Yeasts were found concentrated at the sediment surface and with the highest counts at the most polluted site. Candida krusei, Pichia membranaefaciens and similar species typically forming rugose colonies with radiating ridges were the prevalent yeasts in these sediments, and species like Rhodotorula rubra related to basidiomycetous fungi were found in relatively low numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
0
14
0
2
Order By: Relevance
“…Site 3 was also on Ilha do Fundao, in the channel bordering the mainland and characterized by dark sandy-mud sediment. It had no mangrove vegetation and received raw sewage from a large part of the city of Rio de Janeiro (Hagler et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Site 3 was also on Ilha do Fundao, in the channel bordering the mainland and characterized by dark sandy-mud sediment. It had no mangrove vegetation and received raw sewage from a large part of the city of Rio de Janeiro (Hagler et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…Each sediment sample was mixed with a sterile spatula and subsamples of 50 to 100 g (wet weight) were diluted in 1 to 2 volumes of sterile 0.85% NaCI. After 30 s vortex shaking, heavy particles were allowed to settle and aliquots of the supernatant were used for microbial counts and yeast isolation (Hagler et al, 1982). Seawater was also collected at each site and used directly for microbial counts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, studies about yeasts isolated from sea water began in Florianópolis (11) and later in Recife (27) and Rio de Janeiro (14,15,16). Studies in São Paulo have shown that species of Candida can be used as indicators of pollution in marine estuaries (24).…”
Section: Introductionmentioning
confidence: 99%